2012
DOI: 10.1111/j.1423-0410.2012.01590.x
|View full text |Cite
|
Sign up to set email alerts
|

A new AQP1 null allele identified in a Gypsy woman who developed an anti‐CO3 during her first pregnancy

Abstract: Background and Objectives The Colton blood group antigens are carried by the AQP1 water channel. AQP1−/− individuals, also known as Colton-null since they express no Colton antigens, do not suffer any apparent clinical consequence but may develop a clinically significant alloantibody (anti-CO3) induced by transfusion or pregnancy. Identification and transfusion support of Colton-null patients are highly challenging, not only due to the extreme rarity of this phenotype, the lack of appropriate reagents in most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…RBCs from two individuals of the AQP1null rare phenotype lacking AQP1 (also called Colton-null because AQP1 carries Colton antigens) donated in 1994 have been described [26] , [27] . Control RBCs and RBCs from one Rhnull and three independent UT-Bnull individuals were cryopreserved since 1991 and 2003 respectively in the rare blood collection at the Centre National de Référence des Groupes Sanguins (Paris, France).…”
Section: Methodsmentioning
confidence: 99%
“…RBCs from two individuals of the AQP1null rare phenotype lacking AQP1 (also called Colton-null because AQP1 carries Colton antigens) donated in 1994 have been described [26] , [27] . Control RBCs and RBCs from one Rhnull and three independent UT-Bnull individuals were cryopreserved since 1991 and 2003 respectively in the rare blood collection at the Centre National de Référence des Groupes Sanguins (Paris, France).…”
Section: Methodsmentioning
confidence: 99%
“…While this paper was under review, the same allele was found in a Gypsy family; this AQP1 null CO*A(601delG) allele 16 is provisionally designated CO*01N.06 and joins five other silencing null alleles that have been characterized for AQP1 to date.…”
Section: Discussionmentioning
confidence: 78%